An updated RT-qPCR assay for the simultaneous detection and quantification of chikungunya, dengue and zika viruses (2021)
The real-time reverse transcription-polymerase chain reaction (real-time RT-qPCR) has become a leading technique for the detection and quantification of arboviruses, including Chikungunya, Dengue, and Zika viruses. In this study, an updated real-time RT-qPCR assay was designed and evaluated together with a synthetic positive-control chimeric RNA for the simultaneous detection and quantification of Chikungunya, Dengue, and Zika viruses. Amplification assays were performed to verify the construct integrity and optimal reaction/thermal cycling conditions. The analytical sensitivity of the assay was determined for each virus in single and multiplex reactions, as well as the performance in the detection and viral load quantification of experimental samples. The real-time RT-qPCR assay presented here allowed for the simultaneous detection and quantification of Chikungunya, Dengue, and Zika viruses and could be applied in several studies where the accurate quantification of viral genomes is required.